Copper hexacyanoferrate as a long-life cathode for aqueous aluminum ion batteries - Li, Xiaoya (2023)
Aqueous aluminum ion batteries (AAIBs) have emerged as promising low-cost and energy-dense alternatives to conventional lithium-ion batteries. However, AAIBs exhibit a poor rate capability and limited cycle life owing to the rapid degradation. In this study, a copper hexacyanoferrate (CuHCFe) electrode was introduced into AAIBs with an aluminum trifluoromethanesulfonate aqueous electrolyte. Common aluminum electrolytes were compared to highlight the effects of anions and pure acid solutions were examined to eliminate the concerns on proton. A reversible capacity of 69.35 mAh/g was obtained at 70 mA/g, with 73% capacity maintained at 50 C, exhibiting excellent rate performance. Furthermore, the types of anions played an important role in the electrochemical performance. With triflate anions, the CuHCFe electrode exhibited remarkable cycling stability with a neglectable capacity loss in 3000 cycles (eight months of continuous testing) at 70 mA/g and 70% retention after 2300 cycles at 350 mA/g. Ex situ characterization revealed that both transition metals in CuHCFe were simultaneously involved in the redox reaction with minimal lattice change upon ion insertion/extraction. The results demonstrate the compatibility and potential of CuHCFe cathodes and aluminum triflate electrolytes for AAIBs, which can promote the development of such batteries for electrochemical energy storage.